Learning from Catastrophe: Institutional Adaptation in Indonesia's Disaster Response from the 2004 Tsunami to the 2025 Sumatra Crisis - Pambagyo, Wahyu Dwi; Husein, Rahmawati; Paksi, Arie Kusuma; Jabar, Melvin Allen (Journal of Governance and Public Policy, 2026)
This study examines how Indonesia's experience of receiving extensive international humanitarian assistance following the 2004 Aceh tsunami influenced the government's decision to reject foreign aid during the 2025 Sumatra floods. Although disaster governance research has extensively examined international aid coordination and post-disaster reconstruction, limited attention has been paid to how historical disaster experiences reshape state identity and sovereignty norms, which subsequently influence foreign aid policies. Drawing on Alexander Wendt's constructivist framework, this study conceptualizes disaster response as a socially constructed policy shaped by collective learning and evolving national identity. Employing a qualitative exploratory design, the research analyzes government documents, academic literature, policy reports, and media sources published between 2004 and 2025 using qualitative content analysis and process tracing. The findings reveal that coordination difficulties, legal ambiguities, and dependence on external actors experienced during the 2004 tsunami reconstruction became institutionalized as collective policy memory, reinforcing an autonomy-oriented national identity that informed Indonesia's decision to limit foreign humanitarian assistance during the 2025 Sumatra floods. While this policy strengthened the government's commitment to national sovereignty and domestic disaster-management capacity, it also generated tensions between humanitarian imperatives and political independence. The study advances constructivist disaster governance by demonstrating that major disasters function not only as learning events but also as identity-forming processes that reshape state preferences regarding humanitarian intervention and international cooperation. These findings contribute to broader debates on disaster diplomacy, humanitarian governance, and the politics of sovereignty in developing countries.